RANCANGAN ACAK LENGKAP DAN RANCANGAN ACAK KELOMPOK PADA BIBIT IKAN - Bayu Satria Adinugraha; Taswati Nova Wijayaningrum (Universitas Muhammadiyah Semarang, 2017)
Balai Benih Ikan (BBI) is the Unit Pelaksana Teknis Daerah (UPTD) under themanagement and supervision of the Regency or City, which is responsible forimplementing the technique of fish seeding, organizing the function of seed techniqueand seed distribution, parent stock distribution, application of fish and environmentalresources conservation techniques, pest and disease control techniques, and seedquality control through the implementation of fish seed quality system certification.However, of all the fish seeds in this Balai Benih Ikan Purwogondo has different orvariations. To know the cause of variation on fish seedlings at Balai Benih IkanPurwogondo by using experimental design. The method of analysis used is CompletelyRandomized Design Method to know the effect between treatment and RandomizedBlock Design to know the influence between treatment and influence between groupsby manual calculation and see output in the Analysis of Variance table. Keywords: Fish Seeds, Completely Randomized Design, Group Randomized Design,Experimental Design